Effective security management - Sennewald, Charles A., 1931-; Baillie, Curtis (Elsevier, BH, 2016)
"Effective Security Management, Sixth Edition teaches practicing security professionals how to build their careers by mastering the fundamentals of good management. The author, Charles Sennewald, brings common sense, wisdom, and humor to this bestselling introduction to security management that is ideal for both new and experienced security managers. The sixth edition of this classic professional reference work on the topic includes newly updated and expanded coverage of topics such as the integration of security executive into the business, background checks and hiring procedures, involvement in labor disputes, organized crime, and the role of social media."--Resumé vydavatele
Keywords: bezpečnostní management; bezpečnostní služby; safety management; security services; příručky; elektronické knihy; handbooks, manuals, etc; electronic books